Climate Change and Individual Behavior - René Bernard; Panagiota Tzamourani; Michael Weber (SUERF - The European Money and Finance Forum, 2022)
Climate change poses large economic costs to governments and societies. Reducing individuals' CO2 footprints is central in mitigating climate change. In a new paper, we show that providing information on combating climate change motivates individuals to take costly actions to offset CO2 emissions. Presenting the information as the result of scientific research is as effective as framing it as the behaviour of other people. Individuals' responses vary depending on their socio-demographic characteristics and attitudes towards climate change. Furthermore, individuals choose information that aligns with their views. Individuals who actively gather information about climate change have a higher willingness to pay for carbon offsets.
Keywords: D10; D83; D91; Q54; 330; Climate change; information treatment; willingness to pay; information acquisition; CO2 compensation